Perchlorate-reducing bacteria from Antarctic marine sediments (2022)
Perchlorate is a contaminant that can persist in groundwater and soil, and is frequently detected in diferent ecosystems at concentrations relevant to human health. This study isolated and characterised halotolerant bacteria that can potentially perform perchlorate reduction. Bacterial microorganisms were isolated from marine sediments on Deception, Horseshoe and Half Moon Islands of Antarctica. The results of the 16S ribosomal RNA (rRNA) gene sequence analysis indicated that the isolates were phylogenetically related to Psychrobacter cryohalolentis, Psychrobacter urativorans, Idiomarina loihiensis, Psychrobacter nivimaris, Sporosarcina aquimarina and Pseudomonas lactis. The isolates grew at a sodium chloride concentration of up to 30% and a perchlorate concentration of up to 10,000 mg/L, which showed their ability to survive in saline conditions and high perchlorate concentrations. Between 21.6 and 40% of perchlorate was degraded by the isolated bacteria. P. cryohalolentis and P. urativorans degraded 30.3% and 32.6% of perchlorate, respectively. I. loihiensis degraded 40% of perchlorate, and P. nivimaris, S. aquimarina and P. lactis degraded 22%, 21.8% and 21.6% of perchlorate, respectively. I. loihiensis had the highest reduction in perchlorate, whereas P. lactis had the lowest reduction. This study is signifcant as it is the frst fnding of P. cryohalolentis and. P. lactis on the Antarctic continent. In conclusion, these bacteria isolated from marine sediments on Antarctica ofer promising resources for the bioremediation of perchlorate contamination due to their ability to degrade perchlorate, showing their potential use as a biological system to reduce perchlorate in highsalinity ecosystems.